2017
DOI: 10.35609/jmmr.2017.2.4(4)
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Research Self-Efficacy and Research Productivity through Research Culture Implementation

Abstract: Objective - This study aims to determine the conditions relating to research culture, research self-efficacy and research productivity at private universities in Riau, Indonesia, to examine the direct and indirect influences among research culture, research self-efficacy and research productivity. Methodology/Technique - A questionnaire was used to obtain responses from lecturers at 12 private universities (with a total of 349 responses). The data collected from the sample was analysed using structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Prior research demonstrated a positive influence of RSE on research related outcomes in higher education (Adekunle, 2022; Gaoat, 2022; Ocampo et al. , 2022; Zhang, 2022; Garnasih et al. , 2017; Hemmings and Kay, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research demonstrated a positive influence of RSE on research related outcomes in higher education (Adekunle, 2022; Gaoat, 2022; Ocampo et al. , 2022; Zhang, 2022; Garnasih et al. , 2017; Hemmings and Kay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research demonstrated a positive influence of RSE on research related outcomes in higher education (Adekunle, 2022;Gaoat, 2022;Ocampo et al, 2022;Zhang, 2022;Garnasih et al, 2017;Hemmings and Kay, 2009). Academics with higher levels of RSE are more likely to produce more, whereas those with low RSE tend to produce less research output (Livinƫi et al, 2021;Nazari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human-organizational dichotomy is a widely recognized framework for identifying driving factors of RP. Drivers under the "human" category include research skills and competence [11], self-efficacy [12], global innovativeness [13], individual factors [10], self-determination [14], mentoring [15], and dynamics of professional life [16], among others. On the other hand, organizational factors include institutional support [17], departmental culture [18], tenure and promotions [19], research-oriented culture [19], and situational factors [20].…”
Section: Introductionmentioning
confidence: 99%